Double-pulse nanosecond laser ablation of silicon in water. (12th June 2015) - Momeni, A; Mahdieh, M H
Abstract: This work was conducted experimentally to investigate the material removal rate and its mechanisms during the single-pulse and double-pulse nanosecond laser ablation of a silicon wafer in distilled water. The laser ablation processes were performed under the same experimental conditions with the same total pulse energy ( E single pulse = E double pulse ). The amount of ablated material was estimated for all of the processes based on measuring the dimensions (depths and widths) and volumes of the laser-induced craters on the silicon wafer. The results indicate that double-pulsed laser processing can result in a higher material removal rate compared to the more common single-pulse process, when the inter-pulse delay time is less than the pulse duration. The higher ablation yield in the double-pulse process can be due to the higher coupling efficiency of the second laser pulse with the melted target induced by the laser pre-pulse, leading to the more efficient laser energy absorption and deposition within the irradiated region. The double-pulse nanosecond laser processing with delay time of ~5 ns not only results in a higher material removal rate, but also leads to preparation of silicon nanoparticles with a greater mean particle size compared to that of the more common single-pulse laser ablation process.